VITAMINS - qizi, Murodillayeva Ruxshona Jasurbek; Bakhtiyarovich, Asatullayev Rustamjon (Research Focus International Scientific Journal, 2026)
Vitamins are essential micronutrients required for maintaining normal physiological functions in the human body. Although needed in small amounts, they play a crucial role in metabolism, immunity, and overall well-being. This article explores the types of vitamins their biological functions, and the consequences of deficiencies. The study highlights the importance of a balanced diet to ensure adequate vitamin intake and prevent related health issues.